1990
DOI: 10.1590/s0074-02761990000100012
|View full text |Cite
|
Sign up to set email alerts
|

Human and dogs Toxocara canis infection in a poor neighborhood in Bogota

Abstract: Prevalence of Toxocara canis antibodies was studied in a poor community of Bogotá, Colombia. Two-hundred-seven patients, from both sexes and all age groups, were studied. Positive ELISA titers were found in 47.5% of the population, a high prevalence compared with reports from developed countries. T. canis ova were positive in 43.6% of fecal samples from dog puppies. An endemic pattern of the disease is described: socioeconomic status, weather, pollution, poor hygiene and a significant population of infected do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
24
0
16

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 0 publications
6
24
0
16
Order By: Relevance
“…On the other hand, the use of public parks or places by those people were highly associated with the positive serology (p < 0.001), suggesting that Toxocara eggs might be present in those places and to be a main source for infection in this population. Canine feces are frequent in public places and playgrounds in other countries, as reported by other authors around the world 1,5,15,22,24,33 . Although limited studies about soil contamination with Toxocara eggs in Peru have revealed a frequency ranging from 30% to 80% 19 .…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, the use of public parks or places by those people were highly associated with the positive serology (p < 0.001), suggesting that Toxocara eggs might be present in those places and to be a main source for infection in this population. Canine feces are frequent in public places and playgrounds in other countries, as reported by other authors around the world 1,5,15,22,24,33 . Although limited studies about soil contamination with Toxocara eggs in Peru have revealed a frequency ranging from 30% to 80% 19 .…”
Section: Discussionsupporting
confidence: 62%
“…Some nematode parasites of animals can infect noncompatible hosts such as humans (Agudelo et al 1990, Bouchard et al 1994, Buijs et al 1994, Gueglio et al 1994) and remain in their organisms as migrating larvae arrested in their development but metabolically active (Pezzani et al 1993), eliciting mechanical damages that are exacerbated by the host's immune response (Agudelo et al 1990, Hirata et al 1990). …”
mentioning
confidence: 99%
“…canis is very common in dogs throughout the world (Agudelo et al 1990). It is the primary cause of VLM in humans (Sánchez et al 1994).…”
mentioning
confidence: 99%
See 2 more Smart Citations